MODEL TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA PERMAINAN PLETOKAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Nita Mustika Sari; Siti Masfuah; Sekar Dwi Ardianti (Universitas Majalengka, 2020)
This study aims to describe the TGT model assisted by petting games to improve students' critical thinking skills. This class action research will be carried out in class IV SDN Pati Wetan 03 with research subjects 35 students and teachers planned in 2 cycles. Data collection techniques in this study were observation, interview, documentation, and test techniques. Analysis of the data used is quantitative and qualitative analysis. Results Increased student learning activities attitudes in the first cycle of 75.5 and increased in the second cycle to 80.5. Whereas the students' learning activities aspects of skills in the first cycle amounted to 70.5 and increased in the second cycle to 79.7. Increased students' critical thinking skills in the first cycle by 70.2 and increased in the second cycle to 81.6. The results of the study can be concluded that the results of the application of the model assisted by plete playing media can improve students' critical thinking skills. Keywords: Teams Games Tournament, Pletokan Games, Critical Thinking Ability